STUDI KUALITATIF PERAN KADER DALAM SKRINING DAN PEMANTAUAN PREEKLAMSIA DI KOMUNITAS - Johariyah - Johariyah (Jurnal Kesehatan Karya Husada, 2021)
Introduction: The maternal mortality rate in Indonesia is 305/100,000 live births, that one cause of this is preeclampsia/eclampsia. Lack of early detection of preeclampsia can cause late treatment. Every midwife who works in the community is assisted by Community Health Volunteers(CHV’s). Objective: The purpose of this study is to determine the role of CHVs in the screening and monitoring of high-risk pregnancies at the community level in Cilacap District.Methods: This qualitative study was conducted through data collection using semi-structured in-depth interviews with 4 CHVs and 10 midwives at​​ two Primary Health Centers in the Cilacap district, Central Java, Indonesia. The content analysis used Open Code software. Results: Four themes were identified in this study: 1) High workload of Midwives, 2) CHVs have easy access to mothers, 3) CHVs are accepted by the community, and 4) CHVs can monitor maternal health in the community. Besides their main tasks, village midwives in Indonesia also provide many programs at Primary Health Centers.